Analysis Of The Influence Of Student Perceptions On The Use Of Bri Mobile (Brimo) In Registering Tuition Fees - Monique Aurelia Nango Agolmen (WINTER JOURNAL: IMWI STUDENT RESEARCH JOURNAL, 2024)
This research aims to determine the influence of perceptions or views regarding usefulness, ease of use, security, and risk on the decision to use BRI Mobile (BRImo). This type of research is explanatory research which explains the causal relationship between variables through hypothesis testing. This research used a population of 107 and a sample of 85 respondents determined based on the Slovin formula. This population is University of Timor (UNIMOR) students who use BRI Mobile to pay tuition fees. Primary data was obtained by distributing questionnaires to 85 FEB Unimor students using BRImo. The analysis technique used is hypothesis testing using the T-test and F-test and multiple linear regression. Data analysis was assisted using IBM SPSS statistics for Windows version 29 and Microsoft Office Excel 2007. From the results of testing the four hypotheses, it can be concluded that the variables of perceived usefulness and ease of use do not influence the decision to use BRImo, while perceptions of security and risk influence the decision to use BRImo. This means that interest in using BRI Mobile is still not commonly used by UNIMOR students due to a lack of knowledge about the benefits and ease of using BRImo and the increasing number of trust issues regarding misuse of online payment applications.